Answer:
2 1/6 lbs. of chicken left
Step-by-step explanation:
4 1/2 - 2 1/3
9/2 - 7/3
27/6 - 14/6
13/6 = 2 1/6
Answer:
Dorsey = 4.8 hours
Campbell = 24 hours
Step-by-step explanation:
It takes "x" hours for Dorsey
So, it will take 5 times more for Campbell, so
It takes "5x" hours for Campbell
Rate is inverse of time, so rates are:
Dorsey: 1/x
Campbell: 1/5x
We know Rate * Time = Work
When together, it takes 4 hours to finish a work, so we can write:
![(\frac{1}{x}+\frac{1}{5x})4=1](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7Bx%7D%2B%5Cfrac%7B1%7D%7B5x%7D%294%3D1)
Solving for x, we get the time of Dorsey:
![(\frac{1}{x}+\frac{1}{5x})4=1\\(\frac{1}{x}+\frac{1}{5x})=\frac{1}{4}\\\frac{5+1}{5x}=\frac{1}{4}\\\frac{6}{5x}=\frac{1}{4}\\5x=24\\x=4.8](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7Bx%7D%2B%5Cfrac%7B1%7D%7B5x%7D%294%3D1%5C%5C%28%5Cfrac%7B1%7D%7Bx%7D%2B%5Cfrac%7B1%7D%7B5x%7D%29%3D%5Cfrac%7B1%7D%7B4%7D%5C%5C%5Cfrac%7B5%2B1%7D%7B5x%7D%3D%5Cfrac%7B1%7D%7B4%7D%5C%5C%5Cfrac%7B6%7D%7B5x%7D%3D%5Cfrac%7B1%7D%7B4%7D%5C%5C5x%3D24%5C%5Cx%3D4.8)
Dorsey takes 4.8 hours alone
Campbell takes 4.8 * 5 = 24 hours alone
Una linea recta ( cualquier eje coordenado es una línea recta) queda definida si se conocen dos puntos que están sobre ella.
Solución:
Ecuación del eje x y = 0
Ecuación del eje y x = 0
Para darle respuesta a la pregunta podemos seguir el siguiente procedimiento:
- Escogemos dos puntos arbitrarios sobre el eje x, por ejemplo
P ( 2 ; 0 ) y Q ( 5 ; 0 ) ( todos los puntos sobre el eje x tienen coordenada y = 0.
Según la cual m = (y₂ - y₁)/ ( x₂ - x₁ ) m = 0
- Usamos la ecuación pendiente-Intercepto
y = m×x + b donde m es la pendiente y b el intercepto con el eje y
y entonces tenemos:
- m = 0 b ( 0 ; 0 )
- Por sustitución en la ecuación pendiente-intercepto
y = 0
Procediendo de forma similar obtendremos la ecuación del eje y
P´( 0 ; 4 ) Q´( 0 : 8 ) entonces
y = m×x + b
En este caso, la pendiente no es definida ( tang 90° ) y b es de nuevo el punto b ( 0 ; 0).
A partir de que todos y cada uno de los puntos sobre el eje y son de valor 0 para x, concluímos que ecuación del eje y es
x = 0
Enlaces de interés:brainly.com/question/21135669?
.166 and with 6 repeating <span />
Using simpler trigonometric identities, the given identity was proven below.
<h3>
How to solve the trigonometric identity?</h3>
Remember that:
![sec(x) = \frac{1}{cos(x)} \\\\tan(x) = \frac{sin(x)}{cos(x)}](https://tex.z-dn.net/?f=sec%28x%29%20%3D%20%5Cfrac%7B1%7D%7Bcos%28x%29%7D%20%5C%5C%5C%5Ctan%28x%29%20%3D%20%5Cfrac%7Bsin%28x%29%7D%7Bcos%28x%29%7D)
Then the identity can be rewritten as:
![sec^4(x) - sen^2(x) = tan^4(x) + tan^2(x)\\\\\frac{1}{cos^4(x)} - \frac{1}{cos^2(x)} = \frac{sin^4(x)}{cos^4(x)} + \frac{sin^2(x)}{cos^2(x)} \\\\](https://tex.z-dn.net/?f=sec%5E4%28x%29%20-%20sen%5E2%28x%29%20%3D%20tan%5E4%28x%29%20%2B%20tan%5E2%28x%29%5C%5C%5C%5C%5Cfrac%7B1%7D%7Bcos%5E4%28x%29%7D%20-%20%5Cfrac%7B1%7D%7Bcos%5E2%28x%29%7D%20%20%3D%20%5Cfrac%7Bsin%5E4%28x%29%7D%7Bcos%5E4%28x%29%7D%20%20%2B%20%5Cfrac%7Bsin%5E2%28x%29%7D%7Bcos%5E2%28x%29%7D%20%5C%5C%5C%5C)
Now we can multiply both sides by cos⁴(x) to get:
![\frac{1}{cos^4(x)} - \frac{1}{cos^2(x)} = \frac{sin^4(x)}{cos^4(x)} + \frac{sin^2(x)}{cos^2(x)} \\\\\\\\cos^4(x)*(\frac{1}{cos^4(x)} - \frac{1}{cos^2(x)}) = cos^4(x)*( \frac{sin^4(x)}{cos^4(x)} + \frac{sin^2(x)}{cos^2(x)})\\\\1 - cos^2(x) = sin^4(x) + cos^2(x)*sin^2(x)\\\\1 - cos^2(x) = sin^2(x)*sin^2(x) + cos^2(x)*sin^2(x)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bcos%5E4%28x%29%7D%20-%20%5Cfrac%7B1%7D%7Bcos%5E2%28x%29%7D%20%20%3D%20%5Cfrac%7Bsin%5E4%28x%29%7D%7Bcos%5E4%28x%29%7D%20%20%2B%20%5Cfrac%7Bsin%5E2%28x%29%7D%7Bcos%5E2%28x%29%7D%20%5C%5C%5C%5C%5C%5C%5C%5Ccos%5E4%28x%29%2A%28%5Cfrac%7B1%7D%7Bcos%5E4%28x%29%7D%20-%20%5Cfrac%7B1%7D%7Bcos%5E2%28x%29%7D%29%20%3D%20cos%5E4%28x%29%2A%28%20%5Cfrac%7Bsin%5E4%28x%29%7D%7Bcos%5E4%28x%29%7D%20%20%2B%20%5Cfrac%7Bsin%5E2%28x%29%7D%7Bcos%5E2%28x%29%7D%29%5C%5C%5C%5C1%20-%20cos%5E2%28x%29%20%3D%20sin%5E4%28x%29%20%2B%20cos%5E2%28x%29%2Asin%5E2%28x%29%5C%5C%5C%5C1%20-%20cos%5E2%28x%29%20%3D%20sin%5E2%28x%29%2Asin%5E2%28x%29%20%2B%20cos%5E2%28x%29%2Asin%5E2%28x%29)
Now we can use the identity:
sin²(x) + cos²(x) = 1
![1 - cos^2(x) = sin^2(x)*(sin^2(x) + cos^2(x)) = sin^2(x)\\\\1 = sin^2(x) + cos^2(x) = 1](https://tex.z-dn.net/?f=1%20-%20cos%5E2%28x%29%20%3D%20sin%5E2%28x%29%2A%28sin%5E2%28x%29%20%2B%20cos%5E2%28x%29%29%20%3D%20sin%5E2%28x%29%5C%5C%5C%5C1%20%3D%20sin%5E2%28x%29%20%2B%20cos%5E2%28x%29%20%3D%201)
Thus, the identity was proven.
If you want to learn more about trigonometric identities:
brainly.com/question/7331447
#SPJ1